Mini plastic injection moulding / Muhammad Arsyad Nashrol Azam and Mohd Fadzli Ismail - Nashrol Azam, Muhammad Arsyad; Ismail, Mohd Fadzli (School of Mechanical Engineering, 2022)
For the creation of plastic parts, injection moulding is the most often utilised manufacturing process. Injection moulding is used to create a vast range of items that differ widely in size, intricacy, and application. An injection moulding machine, raw plastic material, and a mould are all required for the injection moulding process. In the injection moulding machine, the plastic is melted and then injected into the mould, where it cools and solidifies into the final product. For this study, it will discuss the mini plastic injection moulding which is smaller than the real machine. The usage is the same as the machine injection moulding but the speciality of the mini plastic injection moulding is it is small from the real machine. It is also light to carry everywhere and it is cheap. The usage is the same as the machine, which can be injected from the raw material, plastic melt, then the melt plastic will solidify at the mould that had been designed. So, from that result it can get some useful items that are made from plastic. But it can be beneficial for everyone. In conclusion, the project of mini plastic injection moulding can inject the raw material plastic into a mould and from that it will be a useful item